ANALISIS PERLAKUAN DAN PELAPORAN AKUNTANSI BARANG MILIK NEGARA PADA KANTOR WILLAYAH KEMENTERIAN AGAMA PROVINSI SULAWESI UTARA - Albar, Muamar; Morasa, Jenny; Walandouw, Stanly Kho (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
State-Owned Country (BMN/D) is an important element in the government’s performance especially in providing servant to the public, central or local government, which must manage the BMN/D in order to be useful for the government and society. BMN/D’s Management is a process in manage pre-existing wealth or obtained from APBN/D expenses or other legal result that can be used in government and society’s activities. The classification BMN consists of, inventory, land, equipment and machine, buildings and construction, roads, irrigation and networks, construction in progress, and other fixed assets. The government has implemented procurement of good’s which is financed from (APBN). This study is aims to determine the accounting treatment and reporting for state-owned country (BMN) at the Regional representative Office of the Ministry of Religious Affairs in North Sulawesi Province. The research used descriptive method which aims that each data collected is analyzed, then drawn a conclusion and this type of research is qualitative descriptive. The results of this study is accounting treatment of state-owned country at  the Regional representative Office of the Ministry of Religious Affairs in North Sulawesi Province has been based on accrual and  the office’s reporting already in accordance with SAP (Government Accounting Standard) technical bulletin number 15.Keywords: Treatment, Accounting Reporting, BMN